Resistance of Sabi and Dorper ewes to gastro-intestinal nematode infections in an African semi-arid environment - Matika, O.; Nyoni, S.; Wyk, J.B. van; Erasmus, G.J.; Baker, R.L. (2003)
Sabi and Dorper ewes were evaluated for resistance to gastro-intestinal nematode parasites (predominantly Haemonchus contortus) at the Matopos Research Station in Zimbabwe. Live weights (LWT), blood packed red cell volume (PCV) and faecal egg counts (FEC) were recorded at mating, 1 month before lambing and 1-3-month post-lambing for five separate lambings between 1996 and 2000. Dorper ewes were heavier (P<0.01) than Sabi ewes at all sampling times. Sabi ewes were more resistant to internal parasites than Dorper ewes as shown by their significantly lower FEC and significantly higher PCV at all sampling times except at 2-month post-lambing for FEC and at weaning (3-month post-lambing) for PCV. At all sampling times except at weaning individual ewes were treated with an anthelmintic when their FEC was greater than 1500eggs/g (epg) and/or their PCV was less than 20%. The proportion of Dorper ewes that was treated with anthelmintic was significantly higher than that of Sabi ewes at all sampling dates. This effect was particularly marked 1- and 2-month post-lambing. There was a post-parturient rise in FEC in the 2-month period after lambing for both breeds.